PENGARUH IKLAN DI MEDIA SOSIAL INSTAGRAM DAN CELEBRITY ENDORSEMENT TERHADAP MINAT PEMBELIAN ULANG YANG DIMEDIASI OLEH KEPUASAN KONSUMEN PENGGUNA INSTAGRAM: STUDI KASUS DI KABUPATEN SUKOHARJO - Faizal Al Ghani; Irmawati Irmawati (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze the influence of advertising on Instagram social media and celebrity endorsements on repurchase interest mediated by consumer satisfaction of Instagram users. The type of research used in the study uses quantitative methods. The population in this study is Instagram users in Sukoharjo district. The sampling technique in this study is non-probability sampling. Since the number of population is unknown, the calculation needed to find out the minimum number of samples is the Malhottra calculation. Through this Maholtra calculation, the minimum number of samples needed in this study was obtained as many as 100 respondents. This study uses primary data in its preparation. Data was obtained through respondents' answers using a questionnaire type. The data analysis technique in this study uses Partial Least Square (PLS) with the help of SMARTPLS Software. The results of this study are that Ads on Instagram and Celebrity Endorsement have a positive and significant influence on Repeat Purchase Interest. Advertising on Instagram and Celebrity Endorsement has a positive and significant influence on Consumer Satisfaction. Consumer Satisfaction has a positive and significant influence on Repeat Purchase Interest. Ads on Instagram have a positive and significant influence on Repeat Purchase Interest through Consumer Satisfaction. Celebrity Endorsement has a positive and significant influence on Repeat Purchase Interest through Consumer Satisfaction